Perceptions of teachers in Abu Dhabi private schools towards their professional development, its impact on practitioners and students’ performance - ELMANSOURY, MOHAMED SALEH ElSAYED (2018)
Professional development has been widely recognized for its positive effects on teachers’ classroom practices. Voices from worldwide expressed a pressing need for teachers’ engagement in professional development in behalf of students’ performance. This study investigated to what degree Abu Dhabi’s private school teachers have clear perceptions towards their professional development, rewards and obstacles, and whether these programmes are impactful on teachers’ instructional practices or student academic performance. A final point was to test if statistically significant differences exist between teachers and supervisors on their responses to the seven dimensions of the professional development survey. The researcher used the mixed methods to seek answers for 4 research questions. For the quantitative study, a sample comprising of 51 participants from 5 schools was targeted. For the qualitative enquiry, focus group and face to face interviews with 16 teachers and 2 supervisors were conducted. To answer the research questions, a questionnaire was designed with a 5 Likert scale to respond to the first 3 questions of the research, and as to the 4th question, a Man-Whitney comparative test was conducted. The researcher separated the questionnaires of the supervisors (8) to find out significant differences between their answers and those of the teachers’ (43) on the 7 dimensions of the questionnaire. The descriptive statistical packages for social science (SPSS) were the analysis tool. The study yielded the following conclusions: most teachers in private schools rated the professional development as of low impact on their performance or that of their students’; most teachers perceived PD accessible opportunities as focusing on traditional models and periodically held one-shot workshop; most teachers do not view their professional development as rewarding; instead most of them affirmed it put more pressure on their loaded schedule. While most teachers viewed their PD as of low value, most of their supervisors who assumed roles in teaching rated them of high value for all. As to the last question, the study showed that apart from the last two dimensions, there are no significant differences between the responses of both teachers and their supervisors who rated the impact of professional development on student and teacher performance as high while teachers’ rate was low.